Immediate Early Genes, Memory and Psychiatric Disorders: Focus on c-Fos, Egr1 and Arc - Gallo, Francisco T.; Katche, Cynthia; Morici, Juan F.; Medina, Jorge H.; Weisstaub, Noelia V. (Frontiers in Behavioral Neuroscience, 2018)
Many psychiatric disorders, despite their specific characteristics, share deficits in the cognitive domain including executive functions, emotional control, and memory. However, memory deficits have been in many cases undervalued compared with other characteristics. The expression of IEGs such as , c-fos,Egr1 and arc are selectively and promptly upregulated in learning and memory among neuronal subpopulations in regions associated with these processes. Changes in expression in these genes have been observed in recognition, working and fear related memories across the brain. Despite the enormous amount of data supporting changes in their expression during learning and memory and the importance of those cognitive processes in psychiatric conditions, there are very few studies analyzing the direct implication of the IEGs in mental illnesses. In this review, we discuss the role of some of the most relevant IEGs in relation with memory processes affected in psychiatric conditions.